Single Stage Power Control Strategy for Nanogrid Connected Solar PV System - Namani, Rakesh; Natarajan, Babu; Subramaniam, Senthilkumar; Gurusamy, Madhusudanan (Distributed Generation & Alternative Energy Journal, 2022)
The focus on reduction of converter size in nanogrid connected Photo-Voltaic (PV) systems increases to obtain the various advantages. This paper proposes a single stage nanogrid connected solar PV system that works with DC-AC inverter along with the closed loop control strategy to send the maximum power from the PV array. The proposed scheme controls the power delivery of the PV system to nanogrid in a single stage power conversion along with the incorporated Maximum Power Point Tracking (MPPT) controller. The decoupled control strategy has been designed and developed for the proposed system using synchronous reference frame theory. The developed hardware prototype in the laboratory has been used to validate MATLAB/Simulink sim- ulation results. The simulation and experimental results have been observed for dynamic changes in irradiation by maintaining the Total Harmonic Dis- tortion (THD) within the standard limits while operating at unity power factor. The successful validation of the proposed control strategy shows its usefulness in real-time nanogrid applications.